A Coupled Discrete Unified Gas-Kinetic Scheme for Convection Heat Transfer in Porous Media (Communications in Computational Physics, 2020)
In this paper, the discrete unified gas-kinetic scheme (DUGKS) is extendedto the convection heat transfer in porous media at representative elementary volume(REV) scale, where the changes of velocity and temperature fields are described bytwo kinetic equations. The effects from the porous medium are incorporated intothe method by including the porosity into the equilibrium distribution function, andadding a resistance force in the kinetic equation for the velocity field. The proposedmethod is systematically validated by several canonical cases, including the mixedconvection in porous channel, the natural convection in porous cavity, and the natural convection in a cavity partially filled with porous media. The numerical resultsare in good agreement with the benchmark solutions and the available experimentaldata. It is also shown that the coupled DUGKS yields a second-order accuracy in bothtemporal and spatial spaces.